Composition of chromite in the Sakatti Cu-Ni-PGE deposit, Central Lapland Greenstone Belt, Finland - Silventoinen, Saara (Helsingin yliopisto, 2020)
Chromite (Fe2+, Mg)(Cr, Al)2O4 contains in addition to the main elements a variety of minor and trace elements. It often occurs as an accessory mineral in cumulate rich olivine rocks. The melt composition is recorded into crystallised chromite. Due to these characteristics, the composition of chromite can be used as a proxy for the petrogenesis of the magma, providing vital information on how the sulphur saturation occurred, and, in particular, to record the conditions of the cooling cumulates. The Sakatti Cu-Ni-PGE orthomagmatic deposit is located in northern Finland in the CLGB. The deposit is hosted by an olivine cumulate body (the main body), where both disseminated and massive sulphides occur. In addition to the main body, the smaller satellite bodies, the NE and the SW bodies also host mineralisation. The upper barren olivine peridotite body occurs on top of the main body. Thin sections were selected from each of the olivine peridotite bodies (the main, the upper, the NE and the SW body). The chromites can be divided into two groups; unzoned chromites from the main body and the NE body, and zoned chromites from the upper body and the SW body. The chromite grains occur either as intercumulus positions relative to olivine grains or enclosed by unaltered olivine and pyroxene cumulus grains. The elemental compositions, including SiO2, TiO2, Al2O3, Fe2O3, FeO, V2O3, MnO, MgO, ZnO and NiO, of the chromites were analysed using EPMA. The trace element, Ru, was analysed using the LA-ICP-MS. The Sakatti chromites are characterised by variable content of Mg# (0.18 -0.56), moderately high Cr# (0.56 -0.92) and Fe3+# (0.11 -0.50). In addition to Mg# and Cr#, the Al2O3 and TiO2 compositions and textural features, the Sakatti chromites resemble more of those chromites which saturate from komatiitic magmas than chromites which are associated with picritic or basaltic melts. A subset from those chromites that are spatially associated with massive sulphides display high ZnO (> 0.5 wt.%), low Ni (as low as 225 ppm) and ...